2012
DOI: 10.5505/agri.2012.87528
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of TRANSDERMAL FENTANYL for the management of cancer pain in the adults and the elders

Abstract: The TDF patch is a good choice for cancer pain treatment for both adult and geriatric patients. Since it was observed that the incidence of side effects was higher in the geriatric patients, they should be treated more carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…A majority of patients need strong opioid analgesics, which are a tertiary pain treatment in the disease process. 26 In the present study and in a related study, it was observed that cancer patients mainly used tertiary treatment methods (strong opioids) in pain treatment. 27…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A majority of patients need strong opioid analgesics, which are a tertiary pain treatment in the disease process. 26 In the present study and in a related study, it was observed that cancer patients mainly used tertiary treatment methods (strong opioids) in pain treatment. 27…”
Section: Discussionsupporting
confidence: 55%
“…All these changes result in development of physiological responses and increased stress and pain levels. 26 In their study, Ovayolu et al determined that the increased pain level negatively affected general activities, mood, activity level, sleep, and nourishment and impaired the quality of life. 28 Similar to these study results, the present study also revealed that pain experienced by the patients negatively affected their activity level, human relations, quality of life, nourishment, sleeping, and emotional state.…”
Section: Discussionmentioning
confidence: 99%
“…Özel-likle yapılan çalışmalarda opoidlerin kognitif fonksiyonlara üzerine olan olumsuz etkisinin mental durumu kısıtlı geriatrik hastalarda daha belirgin olduğu ve geriatrik hastalarda yan etki sıklığının arttı-ğı gösterilmiştir. [14,15] Bu nedenle geriatrik hastalarda opoid dozu çok daha kontrollü artırılmalıdır.…”
Section: Discussionunclassified